Effect of the Tiger Stripes on the water vapor distribution in Enceladus' exosphere. Issue 12 (23rd December 2014) - Tenishev, Valeriy; Öztürk, Doğa Can Su; Combi, Michael R.; Rubin, Martin; Waite, Jack Hunter; Perry, Mark
Abstract The jet activity emanating from Enceladus' exosphere south pole region observed by Cassini is a subject of intensive study. The in situ and remote sensing observations performed since 2005 triggered an active modeling campaign. Such modeling is essential for better understanding of the measurements performed by individual instruments as well as to link them for a more complete picture of the volatile and ice grain distribution in Enceladus' exosphere. This paper is focused on the investigation of the effect that diffuse gas sources along the Tiger Stripes have on distribution of the water vapor in Enceladus' exosphere using the updated version of our multiplume model. We have found that accounting for the gas production by Tiger Stripes is critical for interpretation of the Cassini data. According to our calculations, sources along the Tiger Stripes (apart from those originally identified by Spitale and Porco (2007)) must contribute about 23–32% to the total plume source rate, which varies in the range of (6.4–29) ×1027 s−1. The effect of the previously unidentified source suggested in the paper is found to be critical for explaining the Ultraviolet Imaging Spectrograph 2007 and 2010 observations in the whole range of the elapsed times.